2021
DOI: 10.1002/ardp.202100188
|View full text |Cite
|
Sign up to set email alerts
|

A novel class for carbonic anhydrases inhibitors and evaluation of their non‐zinc binding

Abstract: In this study, 23 different imidazole derivatives were synthesized, and the inhibitory properties of these derivatives against carbonic anhydrase I and II isoenzymes were investigated for the first time. The inhibition concentrations of the imidazole derivatives were found to be in the range of 2.89–115.5 nM. Docking studies examined the binding properties of the imidazole derivatives, and the structure–activity relationship is discussed. Theoretical calculations showed that the binding mode of the imidazole r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…On the other hand, CA II is expressed in most of tissues including gastrointestinal tract, eye, bone osteoclasts, erythrocytes, testcle, kidney, lung and brain [ 24 ]. The reactions catalyzed by CA isoenzymes are vital in reactions and processes including ion transportation and fatty acid metabolism [ 25 ]. A high level of various CA isoforms in the body is linked to several disorders involving glaucoma, cancer, epilepsy and obesity [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, CA II is expressed in most of tissues including gastrointestinal tract, eye, bone osteoclasts, erythrocytes, testcle, kidney, lung and brain [ 24 ]. The reactions catalyzed by CA isoenzymes are vital in reactions and processes including ion transportation and fatty acid metabolism [ 25 ]. A high level of various CA isoforms in the body is linked to several disorders involving glaucoma, cancer, epilepsy and obesity [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…During the purification and inhibition process of hCA II, esterase activity was examined. The CA II isoenzyme activity was determined by following the change in absorbance at 348 nm [ 105 ].…”
Section: Methodsmentioning
confidence: 99%
“…were found to have good binding energy of −6.4, −7.2, −6.7, and −6.9 kcal/mol, respectively, and proved to be good inhibitors [85] (Scheme 66). negatively charged nitrogen atom of benzenesulfonamide moiety [86] (Scheme 67).…”
Section: S C H E M E 52 Synthesis Of 387(a-u)mentioning
confidence: 99%
“…Synthesized compounds were also subjected to molecular docking studies and 449d and 449i (Ar = trifluoromethylbenzene) were docked into active site of hCA I. Similarly, 450b (R = naphthalene) and 449d were docked into active site of hCA II and it was observed that compounds 449d , 449i , 450b , and 449d were found to have good binding energy of −6.4, −7.2, −6.7, and −6.9 kcal/mol, respectively, and proved to be good inhibitors [ 85 ] (Scheme 66­).…”
Section: Chemistry Of Heterocycles As Ca Inhibitorsmentioning
confidence: 99%